On the Complementarity of Liberalism and Democracy - Viktor J. Vanberg (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik, 2006)
The growth of the democratic welfare state has been accompanied by significant restrictions on individual liberty, raising doubts about the sustainability of the ideals of liberalism in democratic polities. The principal claim of this paper is that, adequately understood, liberalism and democracy represent complementary ideals. The argument in support of this claim is based on a distinction between three levels at which liberalism and democracy can be compared, namely the level of their ?institutional embodiment,? the level of their principal focus, and the level of their underlying normative premise. It is argued that democracy and liberalism share the same fundamental normative premise, namely the principle of individual sovereignty, that they complement each other in their respective principal foci, namely citizen sovereignty and private autonomy, but that frictions between the two ideals have arisen at the level of their institutional implementation. It is conjectured that the threat that the democratic welfare state has posed to the ideals of liberalism must be attributed to particular institutional realizations of the ideal of democracy, not to the ideal itself. It is discussed what kinds of reforms in political institutions are needed in order for liberalism and democracy to be in harmony, not only at the level of their normative premises but also at the level of their institutional implementation.
Keywords: 330